Protecting childhood in the AIDS pandemic finding solutions that work - Heymann, Jody, 1959-; Sherr, Lorraine; Kidman, Rachel (Oxford : Oxford University Press, 2012)
'Protecting Childhood in the AIDS Pandemic' provides lessons from experts around the world on how to transform the outcomes of children affected by HIV/AIDS. It examines which public policies and programs best meet the full range of children's needs, from medical care to social support and from infancy to adolescence.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Keywords: AIDS (Disease) in children